Sustainable Business Models Principles, Promise, and Practice (CSR, Sustainability, Ethics & Governance,, 2018)
This book provides a rich overview and takes a closer look at the current state of theory and practice in the field of sustainable business models. The chapters in this book examine and analyze existing and new approaches towards sustainable business models and showcase the implementation of sustainable business through both quantitative and qualitative studies, including several case studies and many practical examples. It approaches these issues from the standpoints of diverse business disciplines to yield new insights and ideas that are relevant from both an academic and professional perspective. In its essence, the book examines how firms' value creation processes can be driven by sustainability and social responsibility and how this impacts business and society. Readers will find a range of sustainable business models that have been employed and are being pioneered in various industries around the globe - which are thoroughly investigated and discussed, and put into a comprehensive conceptual framework.